As teorias da aprendizagem na Base Nacional Comum Curricular (BNCC): contribuições para ensino da língua portuguesa no ensino fundamental anos finais - Silva, Sonia da (2022)
This article discusses the theories of learning in the National Common Curricular Base (BNCC) and aims to understand this relationship in the teaching of the Portuguese Language Years Finals. Thus, the objective of this work is to analyze the Portuguese Language teaching proposal as recommended by the BNCC, to verify the relationship between learning theories and the normative piece and to investigate their contributions in the light of learning theories for the teaching of the Portuguese Language Finals Years. Thus, through a qualitative approach, a bibliographic search of theorists such as Henri Wallon and Lev Vygostky was carried out. In this perspective, the study reveals the remarkable contribution of these theorists to education and to BNCC in the Teaching of the Portuguese Language Finals Years, mainly in the need for social interaction to favor the learning process.